REPRESENTASI HAK PEREMPUAN ATAS KEHAMILAN TIDAK DIRENCANAKAN DALAM AKUN INSTAGRAM @PERKUMPULAN.SAMSARA - Ghazala, Abida; Wahyudin, Uud; Zein, Duddy (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka Palembang, 2019)
The objectives of this research are: (1) to find out the denotative meaning on the digital poster titled #PerempuanPunyaPilihan which uploaded by the Instagram account of @perkumpulan.samsara, (2) to find out the connotative meaning on the digital poster titled #PerempuanPunyaPilihan which uploaded by the Instagram account of @perumpulan.samsara, and (3) find out the myth on the digital poster titled #PerempuanPunyaPilihan which uploaded by the Instagram account of @perkumpulan.samsara. The results of this research found that the denotation meaning of digital poster titled #PerempuanPunyaPilihan which was uploaded by the Instagram account of @perkumpulan.samsara contained the issue of unplanned pregnancies, how to overcome them, and the viewpoint caused regarding reproductive health rights especially for women. The connotations meaning expressed in the Instagram account of @perkumpulan.samsara is a form of Samsara's support for any women's choice for their reproductive health rights. The myths in @perkumpulan.samsara’s uploaded digital poster are the need for insight into reproductive health and equality of women's rights in Indonesia as well as removing the negative stigmas about unplanned pregnancy.